A Subclass of Harmonic Univalent Functions with Varying Arguments Defined by Generalized Derivative Operator. (19th February 2012) - Eljamal, E. A.; Darus, M.
Abstract : Making use of the generalized derivative operator, we introduce a new class of complex valued harmonic functions which are orientation preserving and univalent in the open unit disc and are related to uniformly convex functions. We investigate the coefficient bounds, neighborhood, and extreme points for this generalized class of functions.